Properties of keruing belimbing-polypropylene composites / Shaikh Abdul Karim Yamani, Jamaludin Kasim and Siti Nor Haslina - Yamani, Shaikh Abdul Karim; Kasim, Jamaludin; Haslina, Siti Nor Haslina (2005)
Malaysian wood industries are producing a lot of waste. These wastes are currently less utilized, thus, creating a problem to the environment. Thus, to reduce these wastes, a study was conducted to include it as filler in thermoplastic composite. The use of scrap-wood derived fillers for thermoplastic has become more accepted by the plastics industry in the recent years. Wood derived fillers have several advantages over their inorganic counterparts. The objectives of the study are to assess the suitability of Keruing Belimbing sawdust as filler in thermoplastic composite manufacture, and to study the effect of particle size and filler content on the composite properties. The findings show that Keruing Belimbing sawdusts are suitable and can be used as filler in manufacturing thermoplastic composite.